Textual Authority Contestation in the Codification of the Uthmanic Muṣḥaf and the Narrative of Ibn Masʿūd’s Rejection - Rozaq Shohibul Ichsan Shohibul; Muhammad Shohib Shohib (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2026)
The codification of the Uthmanic Muṣḥaf is widely regarded as a defining moment in the preservation and standardization of the Qur'anic text. Nevertheless, the process has remained a subject of scholarly debate, particularly regarding the reports that ʿAbd Allāh ibn Masʿūd rejected the official codification under Caliph ʿUthmān ibn ʿAffān. This study investigates the contestation of textual authority reflected in these narratives by examining their historical context, transmission, and interpretation in both classical and contemporary scholarship. Employing a qualitative library research method, the study analyzes primary sources on ḥadīth, qirāʾāt, and ʿulūm al-Qur'ān, complemented by relevant modern academic literature. A historical-critical and discourse analysis approach is applied to distinguish between historical evidence and later ideological constructions. The findings reveal that Ibn Masʿūd’s reported disagreement was primarily related to the process of codification and the status of companion codices rather than a rejection of the authenticity of the Qur'an. Furthermore, later theological and political discourses contributed to the expansion of these narratives, transforming them into competing claims of textual authority. The study concludes that the Uthmanic codification successfully established a unified Qur'anic text while accommodating the recognized diversity of qirāʾāt, thereby ensuring the continuity, authenticity, and authority of the Qur'anic tradition. This research contributes to contemporary Qur'anic studies by offering a critical reassessment of Ibn Masʿūd’s position within the broader discourse on the formation of the Qur'anic canon.